A Reliable and Reproducible Technique for DNA Fingerprinting in Biorepositories: A Pilot Study from BioBIM. Issue 4 (October 2013) - Palmirotta, Raffaele; De Marchis, Maria Laura; Ludovici, Giorgia; Ialongo, Cristiano; Leone, Barbara; Lopez, Nadia; Valente, Maria Giovanna; Spila, Antonella; Ferroni, Patrizia; Della-Morte, David; Guadagni, Fiorella
Standard operating procedures (SOPs) optimization for nucleic acid extraction from stored samples is of crucial importance in a biological repository, considering the large number of collected samples and their future downstream molecular and biological applications. However, the validity of molecular studies using stored specimens depends not only on the integrity of the biological samples, but also on the procedures that ensure the traceability of the same sample, certifying its uniqueness, and ensuring the identification of potential sample contaminations. With this aim, we have developed a rapid, reliable, low-cost, and simple DNA fingerprinting tool for a routine use in quality control of biorepositories samples. The method consists of a double ALU insertion/deletion genotyping panel suitable for uniqueness, identification of sample contaminations, and gender validation. Preliminary data suggest that this easy-to-use DNA fingerprinting protocol could routinely provide assurances of DNA identity and quality in a biorepository setting.